Plays from famous stories and fairy tales; royalty-free dramatizations of favorite children's stories. - Thane, Adele (Plays, inc., 1967)
Twenty-eight plays for young people rendered from well known fairy tales and stories. Includes Rumpelstiltskin; Rapunzel; Heidi; Cinderella; Tom Sawyer, Pirate; and Rip Van Winkle.